Conclusion - Du, Xiaoyu (A+BE | Architecture and the Built Environment, 2019)
The main objective of this dissertation is to find the main factors of building spatial configuration that affecting the thermal summer environment, the possibility of occupants to achieve thermal comfort there in, and to propose a spatial design method as the passive cooling strategy for summer thermal comfort. In accordance with the objective, the research questions were put forward in section 1.5 of chapter 1. For every sub-question, there is a respective chapter to answer it, see figure 1.3 in section 1.6 of chapter 1. In chapter 8, some conclusions of part I of this dissertation were summarised. In this chapter, the research questions are answered. In addition, the limitation of this research and recommendations for future practice and research will be mentioned as well.